Numerical simulation of magnetohydrodynamic buoyancy-induced flow in a non-isothermally heated square enclosure - Öztop, Hakan Fehmi; Oztop, Mesut; Varol, Yasin (Elsevier Science Bv, 2009)
Numerical simulation of magnetohydrodynamic (MHD) buoyancy-induced heat transfer and fluid flow has been analyzcd in a non-isothermally heated square enclosure using finite volume method. The bottom wall of enclosure were heated and cooled with a sinusoidal function and top wall was cooled isothermally. Vertical walls of the enclosure were adiabatic. Effects of Rayleigh number (Ra = 10(4), 10(5) and 10(6)), Hartman number (Ha = 0, 50 and 100) and amplitude of sinusoidal function (n = 0.25, 0.5 and 1) oil temperature and flow fields were analyzed. It was observed that heat transfer was decreased with increasing Hartmann number and decreasing value of amplitude of sinusoidal function. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Natural convection; Non-isothermal wall; Magnetohydrodynamic